Sr Examen

Expresión yzvx¬z

El profesor se sorprenderá mucho al ver tu solución correcta😉

    Solución

    Ha introducido [src]
    (y∧z)∨(x∧(¬z))
    (x¬z)(yz)\left(x \wedge \neg z\right) \vee \left(y \wedge z\right)
    Simplificación [src]
    (x¬z)(yz)\left(x \wedge \neg z\right) \vee \left(y \wedge z\right)
    (y∧z)∨(x∧(¬z))
    Tabla de verdad
    +---+---+---+--------+
    | x | y | z | result |
    +===+===+===+========+
    | 0 | 0 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 0 | 1 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 0 | 0      |
    +---+---+---+--------+
    | 0 | 1 | 1 | 1      |
    +---+---+---+--------+
    | 1 | 0 | 0 | 1      |
    +---+---+---+--------+
    | 1 | 0 | 1 | 0      |
    +---+---+---+--------+
    | 1 | 1 | 0 | 1      |
    +---+---+---+--------+
    | 1 | 1 | 1 | 1      |
    +---+---+---+--------+
    FNCD [src]
    (xz)(y¬z)\left(x \vee z\right) \wedge \left(y \vee \neg z\right)
    (x∨z)∧(y∨(¬z))
    FNC [src]
    (xy)(xz)(y¬z)(z¬z)\left(x \vee y\right) \wedge \left(x \vee z\right) \wedge \left(y \vee \neg z\right) \wedge \left(z \vee \neg z\right)
    (x∨y)∧(x∨z)∧(y∨(¬z))∧(z∨(¬z))
    FND [src]
    Ya está reducido a FND
    (x¬z)(yz)\left(x \wedge \neg z\right) \vee \left(y \wedge z\right)
    (y∧z)∨(x∧(¬z))
    FNDP [src]
    (x¬z)(yz)\left(x \wedge \neg z\right) \vee \left(y \wedge z\right)
    (y∧z)∨(x∧(¬z))